Pengkayaan β-Karoten Mi Ubi Kayu Kayu dengan Tepung Labu Kuning (Cucurbita maxima Dutchenes) - Sri Anggrahini; Ika Rahnawati; Agnes Murdijati (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2006)
Pumpkin is a potential source of/3-carotene, therefore, can be used for )3-carotene enrichment of food such as cassava noodle, and then the cassava noodle can be used to increase the vitamin A intake of people. A base material to make cassava noodles are cassava flour; pumpkin flour and gluten. The objective of the research was to know the effect of the b-carotene enrichment of cassava noodle by pumpkin flour on the cassava noodle characteristics. The enrichment of the cassava noodle was made by adding pumpkin flour in various proportions i.e. 0, 5, 10, 15, and 20%. The cassava noodle were analyzed for the chemical, physical, and sensory propierties. The results showed that the cassava noodle that was enriched by 15 % pumpkin flour could be accepted by panelists. It can supply 147 RE/100 g of0-carotene. The chemical characteristics of cassava noodle were 74,85 % moisture, 2,99% ash, 15,75% protein, 3,44% fat and 77,83% carbohydrate contents.